Mapeamento de parâmetros de soldagem robotizada GMAW visando tempos de produção reduzidos para juntas do aço ASTM A572 G50 - Arbex, João Renato (Universidade Federal de São Carlos, 2022)
The welding process using electric arc with shielding gas (GMAW - Gas Metal Arc Welding) is extremely widespread and used in several applications. This is due to its high productivity combined with low cost in addition to its suitability to high automation level. The technology development for an already traditional process is supported by constant demands. One of the most important is related to increase productivity in the industry so that achieving higher filler material deposition rates. Increasing the travel speed in welding process is one of the most straight through and effective ways to meet this demand. However, as the commonly available processes reach a limit, there is a need of recent technologies to overcome such limitations. As such, for any innovative technology there are challenges to be overcome, which require studies to understand its operation and application in a way that promotes the desired results without compromising the required quality. The goals of this work are increase the welding travel speed so that the cycle times could be reduced. The starting point is to understand the initial state and conduct tests, aiming at achieving high travel speeds through the variation of welding parameters, followed by visual and macrographic analysis looking for defects and meeting specifications of the joints. Changing process from standard pulsed arc to PMC results on a 50% increase on welding travel speed which means an average 32% reduction on process time on the studied case.
Mapping of GMAW robotic welding parameters aiming at reduced production times for ASTM A572 G50 steel joints
Keywords: Soldagem; Welding; Robot weld; Weld speed; Velocidade de soldagem; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::INSTALACOES E EQUIPAMENTOS METALURGICOS